Margelopsis gibbesii (McCrady, 1859) (Cnidaria, Hydrozoa): taxonomic review, and conservation of usage by designation of a lectotype - Calder, Dale R.; Johnson, William S. (Zootaxa, 2015)
The binomen Nemopsis gibbesii McCrady, 1859, originally applied to a species of hydromedusa and its supposed hydroid from South Carolina, USA, has been known for more than a century to encompass two species. The medusa stage is conspecific with that of Nemopsis bachei L. Agassiz, 1849, while the hydroid stage is referable to the genus Margelopsis Hartlaub, 1897. Both that hydroid, and the medusa stage now subjectively linked to it, are commonly assigned to M. gibbesii. With no type having ever been designated for McCrady’s species, a lectotype is designated to stabilize nomenclature of the species and serve as the standard for application of the name. In the absence of type specimens, an illustration of the hydroid of N. gibbesii by McCrady is chosen as lectotype, thereby conserving the name Margelopsis gibbesii in its accustomed usage. Hydroids and medusae of the species are re-described from new material, the cnidome of both stages is characterized, and a taxonomic review is given. The hydroid stage is reported for the first time since its original description in the mid-19th century. Medusae of M. gibbesii are also seen infrequently, having been reported only six times earlier.